Single-cell characterization of anti-LAG-3 and anti-PD-1 combination treatment in patients with melanoma - Huuhtanen Jani; Kasanen Henna; Peltola Katriina; Lönnberg Tapio; Glumoff Virpi; Brück Oscar; Dufva Olli; Peltonen Karita; Vikkula Johanna; Jokinen Emmi; Ilander Mette; Lee Moon Hee; et al. (American Society for Clinical Investigation, 2025)
Background. Relatlimab plus nivolumab (anti–lymphocyte-activation gene 3 plus anti–programmed death 1 [anti–LAG-3+anti–PD-1]) has been approved by the FDA as a first-line therapy for stage III/IV melanoma, but its detailed effect on the immune system is unknown.
Methods. We evaluated blood samples from 40 immunotherapy-naive or prior immunotherapy–refractory patients with metastatic melanoma treated with anti–LAG-3+anti–PD-1 in a phase I trial using single-cell RNA and T cell receptor sequencing (scRNA+TCRαβ-Seq) combined with other multiomics profiling.
Results. The highest LAG3 expression was noted in NK cells, Tregs, and CD8+ T cells, and these cell populations underwent the most significant changes during the treatment. Adaptive NK cells were enriched in responders and underwent profound transcriptomic changes during the therapy, resulting in an active phenotype. LAG3+ Tregs expanded, but based on the transcriptome profile, became metabolically silent during the treatment. Last, higher baseline TCR clonality was observed in responding patients, and their expanding CD8+ T cell clones gained a more cytotoxic and NK-like phenotype.
Conclusion. Anti–LAG-3+anti–PD-1 therapy has profound effects on NK cells and Tregs in addition to CD8+ T cells.